The Comparison Between Plyometrics and Aerobic Exercises toward Medical Students of Diponegoro University - Iin Atika Situngkir; Endang Ambarwati; Endang Kumaidah; Sumardi Widodo (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
ABSTRACTIntroduction: Sedentary life style had become one of factors causing health problem for someone in general. To avoid that condition we could apply some exercises regularly. Exercise can improve concentration, memory, and intellectuals. The sports enjoyed today are Plyometrics and Aerobics. Both sports proved beneficial in improving cognitive function, including concentration. The purpose of this study is to find out comparison between Plyometric and Aerobic towards concentration level.Methods: This research applied quasi-experimental study with pre and post-test design. There were subjects divided into three groups were control group, Plyometrics group and Aerobics group. Medical students of Diponegoro University were taken as subjects of the research which consist 39 males. Intervention is given for 6 weeks. Each week consists of two meetings. The indicator of this research focused on concentration level measured by using Digit Symbol Substitution Test (DSST), measured before and after 6 weeks exercise. Statistical analysis of this study using Paired t-test.Results: There was a significant difference in concentration measurement results between treatment and control groups (p=0.00). Treatment group concentration scores improved better than control group. The DSST score on Plyometrics exercises was 60.00±5.08 and after intervention to 78.00±2.30. The DSST score on Aerobic exercises was 58.76±4.88 and after intervention to 63.07±5.88. Plyometrics exercises are shown to have better effects in increased concentration compared to Aerobic exercises.Conclusion Plyometric and Aerobic exercise were able to enhance concentration level with the highest result achieved by Plyometric group.